2015
DOI: 10.14202/vetworld.2015.727-731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physiological and biochemical responses in different seasons in Surti buffaloes

Abstract: Aim:This study was conducted to evaluate the impact of hot dry, hot humid and comfortable season on physiological, hematological, biochemical, and oxidative stress parameters in Surti buffaloes.Materials and Methods:Ten lactating Surti buffaloes of similar physiological status were selected. Based on the temperature-humidity index (THI), their natural exposure to the environment was categorized as hot dry (THI1), hot humid (THI2) and moderate winter/comfort season (THI3). Blood/serum samples were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 15 publications
12
49
0
Order By: Relevance
“…An elevated value of Hb was also established in thermal stressed southern Nigeria dwarf goats and the observed change may be attributed to higher Hb requirement in the animal to meet the increased oxygen circulation during panting (Okoruwa, 2014). A higher value of total blood Hb concentration was also observed in lactating Surti buffaloes during a hot dry period compared with a hot humid period, and that the increased Hb was correlated to severe dehydration (Chaudhary et al, 2015).…”
Section: Blood Biochemical Responsementioning
confidence: 84%
See 1 more Smart Citation
“…An elevated value of Hb was also established in thermal stressed southern Nigeria dwarf goats and the observed change may be attributed to higher Hb requirement in the animal to meet the increased oxygen circulation during panting (Okoruwa, 2014). A higher value of total blood Hb concentration was also observed in lactating Surti buffaloes during a hot dry period compared with a hot humid period, and that the increased Hb was correlated to severe dehydration (Chaudhary et al, 2015).…”
Section: Blood Biochemical Responsementioning
confidence: 84%
“…These antioxidants scavenge both intracellular and extracellular super oxides and inhibit lipid peroxidation of plasma membrane (Zhang, et al, 2017). Chaudhary et al (2015) reported a significantly higher level of plasma malondialdehyde, SOD and GPx activities in Surti buffaloes during hot humid periods and hot dry periods indicating an increased free radical production during periods of heat stress. In addition to this, plasma antioxidant levels in the hot dry period were significantly higher than in the hot humid period indicating more stressful condition may lead to the elevated synthesis of free radicals (Chaudhary et al, 2015).…”
Section: Blood Biochemical Responsementioning
confidence: 99%
“…Magdub et al (1982) also reported similar result and observed that during heat stress, T3 and T4 levels in plasma and milk decreases. Chaudhary et al (2015) also reported significant decrease in T3 level with increase in THI value. However, Singh et al (1984) reported a significant increase in T3 but in T4 level during heat stress in crossbred cattle.…”
Section: Effect Of Season On Hormonal Assaymentioning
confidence: 81%
“…Magdub et al (1982) reported that heat stress leads to decreased concentrations of triiodothyronine (T3) and thyroxine (T4) in plasma and in milk of lactating cows. Chaudhary et al (2015) also reported significant decrease in T3 level with increase in THI value in Surti buffalo. However, a significant increase in T3 but not in T4 level was observed during heat stress in crossbred cattle (Singh et al, 1984).…”
Section: Introductionmentioning
confidence: 76%
“…Thus, it is possible to assume that the type of breed productivity significantly contributes to testicular testosterone production. It is interesting to note that the levels of triiodothyronine and thyroxine in bulls from the Altai enterprise and in Indian lactating buffalos kept in comfortable temperature and humidity conditions (30) are practically the same, taking into consideration the absence of sex differences in the basal level of these hormones (9).…”
Section: Discussionmentioning
confidence: 99%